2007
DOI: 10.1080/078559818
|View full text |Cite
|
Sign up to set email alerts
|

13 When Group Identities Matter

Abstract: Performance appraisals are a critical part of organizational life, and bias in appraisals is consistently mentioned as a barrier to advancement for diverse workers. This chapter reviews the literature on rater bias in performance appraisals, defined as effects on performance ratings due to ratee category membership. We focus on the major theoretical frameworks (e.g., stereotype fit and relational demography) used in the study of bias, organizing the research findings by the four most commonly studied demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 122 publications
(186 reference statements)
2
25
0
Order By: Relevance
“…Early research on rater bias, specifically halo error, focused on demographic differences such as race or gender (Roberson et al, 2007) indicating the effects of stereotyping and social identity. However, other factors influence the accuracy of performance appraisal ratings (Murphy, 2008).…”
Section: The Dark Triad and Supervisor Ratings Of Performancementioning
confidence: 99%
“…Early research on rater bias, specifically halo error, focused on demographic differences such as race or gender (Roberson et al, 2007) indicating the effects of stereotyping and social identity. However, other factors influence the accuracy of performance appraisal ratings (Murphy, 2008).…”
Section: The Dark Triad and Supervisor Ratings Of Performancementioning
confidence: 99%
“…These were reported by participants themselves. Line managers' age and gender were also controlled for because these may influence performance ratings (Roberson, Galvin & Charles, 2007). Organizational size (1: 10-49, 2: 50-99, 3: 100-149; 4:150-199; 5: 200-249 employees) was also included (the relevant information was provided by our contact in each company, who was either the CEO or another senior officer) because promotion opportunities may be greater in larger organizations.…”
Section: Measures Of Controlsmentioning
confidence: 99%
“…Third, although recent scholarship has suggested the importance of intra-organizational factors in explaining bias at the top (Cortina 2008;Ely and Padavic 2007;Roberson et al 2007), few studies explicitly incorporate the nature of the organizational context as a critical determinant of promotion bias into their conceptualization. Exceptions include Haslam (2007, 2009) and Ryan et al's (2010) studies of women being appointed to high-level, precarious positions in organizations that are in crisis.…”
Section: Extending Prior Researchmentioning
confidence: 97%
“…These scholars contend that more subtle forms of bias, which become particularly pronounced at higher levels of the organization, have replaced the blatant discrimination of earlier decades (Auster 1988(Auster , 1994Cortina 2008;Ely and Padavic 2007;Powell and Butterfield 1997). These studies suggest that tacit mental models drive perceptions and call for a more systematic explorations of intra-organizational bias (Auster 1989;Auster and Drazin 1988;Altman and Shortland 2008;Cortina 2008;Eagly 2005;Eagly and Karau 2002;Ely and Padavic 2007;Roberson et al 2007; Ryan and Haslam 2007). For example, in their study of African American and Hispanic candidates for top management (cabinet level) positions in the U.S. federal government found that mediating the relationship between demographics and promotion decision outcomes are a range of social psychological factors embedded in review committees.…”
mentioning
confidence: 93%
See 1 more Smart Citation